Parâmetros seminais, ultraestruturais, criopreservação e androgênese de espécies do gênero Brycon ameaçadas de extinção - Faustino, Francine [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The doctoral thesis consisted of three main chapters besides the “General Introduction”, which includes a bibliographic review of the species studied and the topics discussed, and the “Final Remarks”. Scientific research articles will be published from the data of the three chapters in the scientific journals listed in the index. The first scientific article (Chapter I) describes the seminal parameters and the spermatozoa structure of Brycon vermelha, “vermelha” (Characiformes, Characidae). The semen of the Brycon vermelha is viscous and contains, in average, 4.34 ± 0.75x1010 spermatozoa.mL-1. Spermatozoa motility was of short duration when activated with distilled water, 46.48 ± 0.07 seconds until 100% of spermatozoa lost their motility. Scanning transmission electron microscopy (STEM) of spermatozoa revealed three distinctive parts: head, middle piece and tail (flagellum). Each part was analysed in detail by transmission electron microscopy (TEM). The characteristics observed suggest that the spermatozoa of B. vermelha posses ancestral characteristics of fish that reproduce by external fertilization, and can thus be classified as “uniflagellate anacrosomal aquasperms”, or aquasperms Type I. These are the first reports on B. vermelha semen and spermatozoa and, therefore, could be used as a reference and benchmark for research studies using biotechniques such as cryopreservation and androgenesis. The second scientific article (Chapter II) describes the ultrastructural alterations of Brycon orbignyanus, “piracanjuba” (Characiformes, Characidae) spermatozoa after cryopreservation. Spermatozoa were cryopreserved for 1 day, 1 month or 1 year in solutions containing DMSO, methyl glycol and methanol. The ultrastructural analysis of the frozen-thawed spermatozoa revealed alterations varying from small damages to the different parts of the cell to total destruction of spermatozoa ...

A Tese de Doutorado foi estruturada em três capítulos, além da “Introdução Geral”, que abrange uma revisão bibliográfica das espécies em estudo e dos temas abordados, e das “Considerações Finais”. Os três capítulos darão origem a artigos científicos em revistas indexadas. O primeiro artigo (Capítulo I) descreve os parâmetros seminais e a ultraestrutura dos espermatozoides de Brycon vermelha, “vermelha” (Characiformes, Characidae). O sêmen da B. vermelha possuiu consistência viscosa, e concentração espermática média de 4,34 ± 0,75x1010 espermatozoides.mL-1. O tempo de motilidade espermática, quando ativado com água destilada, foi curto, sendo necessários 46,48 ± 0,07 segundos para perda da motilidade de 100% dos espermatozoides. A análise dos espermatozoides por MEV revelou três regiões distintas: cabeça, peça intermediária e flagelo, sendo cada região caracterizada detalhadamente em MET. Tais características sugerem que os espermatozoides de B. vermelha apresentam características ancestrais próprias de peixes com fecundação externa classificando-os como “espermatozoides aquáticos uniflagelados anacrossomais”, ou seja, aquasperm do Tipo I. Estas informações são as primeiras em relação ao sêmen e espermatozoides de B. vermelha, podendo ser uma referência para futuros estudos, embasando especialmente pesquisas que adotem biotécnicas, como a criopreservação e androgênese. O segundo artigo (Capítulo II) descreve, ultraestruturalmente, as alterações dos espermatozoides da Brycon orbignyanus, “piracanjuba” (Characiformes, Characidae) durante o processo de criopreservação. O exame ultraestrutural dos espermatozoides descongelados criopreservados em soluções contendo DMSO, metilglicol e metanol, em três tempos de armazenamento (1 dia, 1 mês e 1 ano), revelou a presença de alterações no espermatozoide, variando desde ...
Keywords: Peixe - Reprodução; Brycon; Espermatozóides; Preservação do sêmen; Ultraestrutura (Biologia); Fishes